Aspekte der Geschichte westeuropäischer Lehrerbildung - Graumann, Olga (International Dialogues on Education Journal, 2014)
The history of teacher education is very multi-faceted; therefore it is only possible to point to highlights of its progression. This article indicates some developmental aspects of the history of teacher education in Germany and gives some brief sketches of the history of teacher education in Austria, France, and England, with the intent to provide insight into current educational-policy discussions and developments.